The perfect true copy: manuscript as evidence in seventeenth-century vernacular English news and medical books. Issue 3 (3rd July 2019) - Yale, Elizabeth
Abstract: The seventeenth-century London press proliferated titles purporting to reveal new truths gleaned from secret papers and private mailbags. These books, whether political, religious, or scientific in content, promised to reveal to the reader the complex (and sometimes scandalous) inner workings of political, social, and natural processes. They did so via the mechanism of the "perfect true copy": the printed book or pamphlet that was (or claimed to be) an exact copy of private manuscript papers, whether nabbed or voluntarily released from the mailbags and closets of the prominent, the highborn, the powerful, or the learned. This article investigates the relations between printed copy and manuscript original in two cases where medical, natural philosophical, and political controversy overlapped: the mid-1650s posthumous publication (and forgery) of works by the astrological medical practitioner Nicholas Culpeper and the performance of Valentine Greatrakes, the Irish Stroker, as a faith healer in Restoration London. In each case, controversialists pointed to manuscript material as a secure record that backed up points being made in printed pamphlets and books, even inviting readers to check manuscript originals physically (often referred to as "copy": that from which printed copies were made). These case studies engage with questions of gender and women's credibility in print, authoring, and authorizing, both texts and medical expertise. Within the world of cheap vernacular medical print, and pamphlet controversy, women themselves, as well as male associates, such as stationers and husbands, used women's knowledge and domestic positions—which encompassed their connections to manuscript copy—to certify printed texts and cures.